Relationship between blood Lead status and anemia in Ugandan children with malaria infection - Ambrose Mukisa; Denis Kasozi; Claire Aguttu; Peter C. Vuzi; Joseph Kyambadde (BMC, 2020)
Abstract Background In Uganda, childhood anemia remains a health challenge and is associated with malaria infection as well as iron deficiency. Iron deficiency is intertwined with nutritional status, age and other comorbidities including helminths and Lead toxicity. Environmental Lead levels accounts for one's blood Lead (BL) levels. Blood Lead competitively blocks iron absorption, inhibits hemoglobin (Hb) biosynthesis and elevates free erythrocyte protoporphyrin (FEP) levels. Lead toxicity's contribution towards anemia pathogenesis, especially during malaria infection has not been studied. Concomitant exposure to both malaria infection and Lead pollution, exacerbates the anemia status. This study therefore aimed at expounding the anemia status of these Ugandan children aged under 5years who are exposed to both malaria infection and environmental Lead pollution. Methods Briefly, venous blood samples from 198 children were microscopically assayed for malaria parasite density (PD), and hemoglobin (Hb) concentrations using the cyanmethemoglobin method, while BL and FEP levels were determined by the standard atomic absorption spectrophotometric and fluorometric methods respectively. Results One hundred and fifty-one (76.3%) of the children analyzed had moderate anemia (Hb <10>5 g/dL) with Means of BLL=8.6 µg/dL, Hb =7.5 g/dL, FEP/Hb =8.3 µg/g and PD =3.21×103 parasites / µL, while eight (4%) were severely anemic (<5 g/dL). Regression analysis and statistical correlation between PD and Hb (r = -0.231, R2= 0.15 P-value < 0.001) was negative and weak as compared to that between FEP/Hb and Hb (r = -0.6, R2=0.572 P-value=0.001). Conclusion Based on the study's findings, we conclude that BL significantly contributes to the pathogenesis of anemia and therefore its co-existence with malaria infection in the host exacerbates the anemia status.